Dual-channel spontaneous emission of quantum dots in magnetic metamaterials. - Decker, M; Staude, I; Shishkin, I; Samusev, K; Parkinson, P; Sreenivasan, V; Minovich, A; Miroshnichenko, A; Zvyagin, A; Jagadish, C; Neshev, D; Kivshar, Y (Nature Publishing Group, 2013)
Metamaterials, artificial electromagnetic media realized by subwavelength nano-structuring, have become a paradigm for engineering electromagnetic space, allowing for independent control of both electric and magnetic responses of the material. Whereas most metamaterials studied so far are limited to passive structures, the need for active metamaterials is rapidly growing. However, the fundamental question on how the energy of emitters is distributed between both (electric and magnetic) interaction channels of the metamaterial still remains open. Here we study simultaneous spontaneous emission of quantum dots into both of these channels and define the control parameters for tailoring the quantum-dot coupling to metamaterials. By superimposing two orthogonal modes of equal strength at the wavelength of quantum-dot photoluminescence, we demonstrate a sharp difference in their interaction with the magnetic and electric metamaterial modes. Our observations reveal the importance of mode engineering for spontaneous emission control in metamaterials, paving a way towards loss-compensated metamaterials and metamaterial nanolasers.